−11 Mutation in the ampC Promoter Increasing Resistance to β-Lactams in a Clinical Escherichia coli Strain - Corvec, S. (American Society for Microbiology, 2002)
A mutation was discovered in the Pribnow box of the ampC promoter in a clinical Escherichia coli strain. This −11 C-to-T transition created a perfect homology with the −10 consensus sequence. The new promoter was cloned upstream of the cat gene of pKK232-8 and induced a sixfold increase in promoter strength.